Pre-school Teachers' Opinion on Active Learning - Karlıdağ, İpek Özbay (Bartın Üniversitesi, 2022)
The study was aimed to determined preschool teachers' opinions about active learning. The data of the study were obtained through semi-structured interviews. The study group of the study consists of 10 preschool teachers being selected through purposive sampling. Content analysis method was used in the analysis of the data. As a result of the study, it was seen that teachers defined active learning as a process in which the learner is active, that activates the senses, in which the learning skills develop, in which learner obtain learning experience by doing and living. While teachers stated that the teacher and learner have various responsibilities in active learning; it was observed that they expressed that the small class size, the crowded classes, classroom management problems, lack of materials, and the introvert learners are as challenges to active learning. It was seen that the practices of teachers regarding active learning are asking interesting questions, encouraging children to ask questions, designing activities that stimulate the senses, creating a collaborative classroom environment, and using different teaching techniques.

Bu araştırmada okul öncesi öğretmenlerinin aktif öğrenmeye ilişkin görüşlerinin belirlenmesi amaçlanmıştır. Nitel araştırma deseninde tasarlanmış olan bu araştırmada veriler yarı yapılandırılmış görüşmeler yoluyla elde edilmiştir. Çalışma grubu amaçsal örnekleme yoluyla seçilmiş 10 okul öncesi öğretmeninden oluşmaktadır. Yarı yapılandırılmış görüşmelerden elde edilmiş olan verilerin analizinde içerik analiz yönteminden faydalanılmıştır. Araştırma sonucunda öğretmenlerin aktif öğrenmeyi öğrenenin aktif olduğu, duyuları harekete geçiren ve öğrenenin becerilerinin geliştiği yaparak yaşayarak öğrenme deneyimi olarak tanımladıkları görülmüştür. Okul öncesi öğretmenleri aktif öğrenmede öğretmenin ve öğrenenin çeşitli sorumluluklarının olduğunu belirtirken; sınıf büyüklüğünün küçük olması, sınıf mevcudunun kalabalık olması, sınıf yönetimi sorunları, materyal eksikliği ve öğrenenin içine kapalı olmasını aktif öğrenmenin önündeki engeller olarak ifade ettikleri görülmüştür. Okul öncesi öğretmenlerinin aktif öğrenmeye ilişkin yaptıkları uygulamalar arasında ilginç sorular sorma, çocukları soru sormaya teşvik etme, duyuları harekete geçiren, araştırma yapabilecekleri, düşündüren, merak uyandırıcı ve dikkat çekici etkinlikler tasarlama, işbirlikçi çalışma ortamı yaratma ve farklı öğretim tekniklerini kullanma olduğu görülmüştür.
Okul Öncesi Öğretmenlerinin Aktif Öğrenmeye Yönelik Görüşleri
Keywords: Other Fields of Education; Alan Eğitimleri